Un inusual bloom de Tetraselmis sp. en la Bahía de Valparaíso, Chile - Pizarro, Marlen; Iturriaga, Rodolfo; Silva, Alejandro; Gallegos, Sonia (Gayana Botánica, 2012)
A bloom of Tetraselmis sp. was observed during the first days of January of 2006 in the Valparaiso Bay (32º 57`S; 71º 33`W), producing green coloration of sea and exclusion of phytoplankton species. Previous blooms of Tetraselmis sp. have not been observed in this bay.